Análisis del trabajo no presencial utilizando un enfoque ETCS - Montil Jimenez, Marta; Barcelo Guido, Olga; Bielsa Hierro, Rosa; Olivan Mallen, Jesús (Revista Complutense de Educación, 2007)
Credit ECTS (European Credit Transfer and Accumulation System) is based on hours of dedication that students must assume to obtain the aims of a program. This research goal was to check importance of student’s homework in their first year in Physical Activity and Sport Sciences at Universidad Europea de Madrid to try to look for the right balance student’s weekly homework. Our specific goals are, in one side; generate activities considered homework, including measured average time of dedication for the student. On the other side, to classify activities to be considered homework from different points of view, to have a global vision of qualification acquired the students through their independently accepted activities.
Keywords: High education; Student’s homework; Time of dedication; Teaching coordination